MAIN ENGINE SELECTION OPTIMIZATION ANALYSIS OF THE SHIP CARAKA JAYA III BASED ON ENGINEERING AND ECONOMY COSIDERATIONS - Faustinus, Jamlean (Department of Naval Architecture - Diponegoro University, 2013)
Caraka Jaya III, as sister ships, built in Indonesia in the era 1990, devided into three building phases. Each phase had the different main engine. Especially for the second phase used the MAN B&W 5S26MC as main engine. After several years later, some of the engines were going to have the problems, especially for the pistons and its rings. The selected engine was not the only one that should be used. In accordance with selection the engine, the optimization procrdure offer best solution as compromise. Selecting the main engine is a complicated and time consuming task. The application of Analytic Hierarchy Process (AHP), one of the Multi Criteria Decision Making (MCDM), would promise a powerful tool for main engine selection as well as usual engineering design process. To select the candidate of the main engine it needs more criteria to obtain satisfactory solution. The criteria therefore are developed as pair wise coparison matrix leading to the mathematic solution. Analysis procedure is devided into three levels, namely, (1) criteria, (2) sub-criteria and (3) alternative of the selected engine. A consistency ratio needed as the acceptance criteria to check the solution of the pair wise comparison matrix. The final result obtained from multiplication of all matrixs on analysis, namely, SKL Diesel 8VD29/24AL- 0.149; MaK 9M20 – 0.190; Wartsila 9L20 – 0.088; Wartsila 6SW28 – 0.121; NIIGATA 8PA5L – 0.098; MAN B&W 5S26MC-0.354. According to the result, optimation solution will be MAN B&W 5S26MC or MaK 9M20